KETERKAITAN ELEMEN INFRASTUKTUR TRANSPPORTASI BERKELANJUTAN DALAM RANTAI PASOK KOMODITAS BERAS DI KULON PROGO - Ridayati, Ridayati; Aminto Ardi, Iwan; Retno Hidayati, Solikhah (KURVATEK, 2025)
Adequate and sustainable infrastructure serves as a strong foundation for ensuring the efficiency, effectiveness, and sustainability of the rice supply chain. The rice supply chain is a complex system involving various actors and processes, from farmers to consumers. In-depth studies of this supply chain are crucial given the importance of rice as a staple food. This article aims to provide an overview of the interconnections between infrastructure elements in the rice supply chain. Previous studies on the rice supply chain have been limited to a single perspective, such as from the perspective of farmers as producers or rice as a product. This article attempts to explore new insights by measuring the interconnectedness of key elements in the rice supply chain. The method used is Network Enabling Transport Service (NETS), which is commonly used in the transportation field. Variables studied include infrastructure, traffic, regulations, communication, support services, and skills. The research results show that the weakest link in the rice supply chain network lies in the regulatory variable. Weak regulations can hinder efficiency, fairness, and sustainability in the supply chain. These findings underscore the importance of improving policies and regulations to support better integration of the rice supply chain. Regulations are particularly related to the development of infrastructure for the efficiency and resilience of the rice supply chain in the face of climate change challenges and demand fluctuations. Adequate infrastructure, such as roads, irrigation, and storage, is crucial to ensure the stable availability of quality rice